A Meta-Analysis of Class-Wide Interventions for Supporting Student Behavior. Issue 2 (1st June 2017) - Chaffee, Ruth K.; Briesch, Amy M.; Johnson, Austin H.; Volpe, Robert J.
Abstract: Off-task and disruptive classroom behavior impedes the learning of the children emitting these behaviors as well as the delivery of instruction to the entire class, which may lead to decreased academic achievement and more severe behavior problems. A meta-analysis of the single-case literature was conducted to understand the effectiveness of class-wide interventions in supporting student behavior in general education settings. Twenty-nine studies of K–12 classrooms, published between January 1969 and September 2015, were included for analysis. Two effect sizes, the Hedges, Pustejovsky, and Shadish (2012, 2013 ) d -statistic and Tau-U (Parker, Vannest, Davis, & Sauber, 2011 ), were calculated for relevant studies and designs. The results of a random-effects meta-analysis using the d -statistic resulted in an estimated overall effect of 2.04 (95% CI [1.67, 2.41]) and an overall effect of 0.93 (95% CI [0.87, 0.99]) using Tau-U. The implications of these findings for interventions implemented in the general education classroom are discussed.